(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2026)
Male factor infertility is a multifactorial disorder that affects a significant percentage of infertile couples; however, many of them remain untreated. In recent years, considerable numbers of infertile men have pursued ’herbal remedies’ as an effective treatment. Among ’herbal remedies’, Shatavari – Asparagus racemosus Willd is recommended for male subfertility in Ayurveda medicine. The effect of Shatavari – Asparagus racemosus root powder of Sri Lankan origin was compared with a placebo for the male reproductive potential. The study included 150 subfertile men with Oligospermia, Asthenozoospermia, Teratozoospermia, and Oligoasthenoteratozoospermia (OAT) who were randomized to receive Shatavari 24 g/day (group T) or a similar regimen of placebo (group C) for 6 months, administered daily in the morning before breakfast with cow’s ghee. The two groups were compared for changes in semen parameters. At the end of the study, statistically significant improvements were observed in the Shatavariadmitted group in semen parameters (volume, sperm concentration, motility, and morphology). At the end of the trial, patients in group T had a mean volume of 2.69 ± 0.14 mL, concentration of 53.28 ± 5.50 million/mL and rapid motility of 26.75 ± 1.68% which was statistically significant from the mean of volume 2.10 ± 0.12 mL, concentration of 32.09 ± 2.88 million/mL and rapid motility on 16.84 ± 1.63% in the placebo group (p < 0.001). Normal sperm morphology was 41.12 ± 3.00% and 32.87 ± 2.71% in groups T and C, respectively (p < 0.001). Shatavari statistically significantly improved semen parameters in sub-fertile men with decreased seminal parameters.